Effect of smoking on transient evoked otoacoustic emissions and contralateral suppression - Vinay (Auris, nasus, larynx, 2010)
Abstract Objective The present study compared the amplitudes of transient evoked otoacoustic emissions (TEOAEs) and efferent suppression in smokers and non-smokers taking age into consideration. Methods Fifty smokers and fifty non-smokers who had normal hearing sensitivity with age range of 20–69 years were considered for the present study. TEOAEs were measured in both the groups of subjects across different age groups. The functioning of the efferent auditory system was evaluated in both the groups by recording the TEOAEs in the presence of a contralateral white noise (CWN) of 70 dB SPL. Results Age did not have a significant effect on the TEOAEs amplitude in both the groups of subjects. However, the TEOAEs amplitude was significantly reduced in smokers compared to non-smokers. The results found a significant effect of age on the amplitude of efferent suppression in smokers, however, no significant effect was found in the non-smokers group. Conclusions It was found that the difference in the amplitude of efferent suppression in smokers was significantly greater for each age group between 20 and 49 years compared to each age group from 50 to 69 years. Results have important implication on the damage to the cochlear structures from smoking.